The Impact of Pre-operative Nutritional Status on Outcomes Following Congenital Heart Surgery - Lim, Carey Yun Shan; Lim, Joel Kian Boon; Moorakonda, Rajesh Babu; Ong, Chengsi; Mok, Yee Hui; Allen, John Carson; Wong, Judith Ju-Ming; Tan, Teng Hong; Lee, Jan Hau (Frontiers in Pediatrics, 2019)
Aims and Objectives Malnutrition is common in children with congenital heart disease and may contribute to adverse outcomes. This study evaluates the impact of pre-operative nutritional status on outcomes after congenital heart surgery. Methods We conducted a retrospective cohort study enrolling children under 10 years old who underwent congenital heart surgery at a tertiary children's hospital from 2012 to 2016. Patients who had patent ductus arteriosus ligation only, genetic syndromes or global developmental delay were excluded. Outcome measures included 30-day mortality, intensive care unit (ICU) length of stay (LOS), hospital LOS, duration of mechanical ventilation and number of inotropes used post-operatively. We performed univariate/multivariable logistic regression analysis, adjusting for age, cyanotic cardiac lesion, co-morbidity and Risk Adjustment for Congenital Heart Surgery (RACHS-1) score. Results 302 children of median age 16.2 [interquartile range (IQR) 3.1, 51.4)] months were included. The most common cardiac lesions were ventricular septal defect (27.8%), atrial septal defect (17.9%) and Tetralogy of Fallot (16.6%). Median weight-for-age z-score (WAZ) was -1.46 (IQR -2.29, -0.61), height-for-age z-score (HAZ) was -0.94 (IQR -2.10, -0.10) and body mass index (BMI)-for-age z-score (BAZ) was -1.11 (IQR -2.19, -0.30). In multivariable analysis, there was an increased risk of 30-day mortality for WAZ ≤ -2 versus WAZ > -2 (adjusted odds ratio (aOR): 4.01, 95% CI: 1.22, 13.13; p=0.022). For HAZ ≤ -2 versus HAZ > -2, there was increased risk of hospital LOS ≥ 7 days (aOR: 2.08, 95% CI: 1.12, 3.89; p=0.021), mechanical ventilation ≥ 48 hours (aOR: 2.63, 95% CI: 1.32, 5.24; p=0.006) and of requiring ≥ 3 inotropes post-operatively (aOR: 3.00, 95% CI: 1.37, 6.59; p=0.006). Conclusion In children undergoing congenital heart surgery, WAZ ≤ -2 is associated with higher 30-day mortality, while HAZ ≤ -2 is associated with longer durations of hospital LOS and mechanical ventilation, and increased risk of use of 3 or more inotropes post-operatively. Future studies are necessary to develop safe and efficacious peri-operative nutritional interventions, particularly in patients with WAZ and HAZ ≤ -2.